Circulating tumour cells and pathological complete response: independent prognostic factors in inflammatory breast cancer in a pooled analysis of two multicentre phase II trials (BEVERLY-1 and -2) of neoadjuvant chemotherapy combined with bevacizumab. (18th October 2016) - Pierga, J.-Y.; Bidard, F.-C.; Autret, A.; Petit, T.; Andre, F.; Dalenc, F.; Levy, C.; Ferrero, J.-M.; Romieu, G.; Bonneterre, J.; Lerebours, F.; Bachelot, T.; et al.
Abstract: Background: We present a pooled analysis of predictive and prognostic values of circulating tumour cells (CTC) and circulating endothelial cells (CEC) in two prospective trials of patients with inflammatory breast cancer (IBC) treated with neoadjuvant chemotherapy combined with neoadjuvant and adjuvant bevacizumab. Patients and methods: Nonmetastatic T4d patients were enrolled in two phase II multicentre trials, evaluating bevacizumab in combination with sequential neoadjuvant chemotherapy of four cycles of FEC followed by four cycles of docetaxel in HER2-negative tumour (BEVERLY-1) or docetaxel and trastuzumab in HER2-positive tumour (BEVERLY-2). CTC and CEC were detected in 7.5 and 4 ml of blood, respectively, with the CellSearch System. Results: From October 2008 to September 2010, 152 patients were included and 137 were evaluable for CTC and CEC. At baseline, 55 patients had detectable CTC (39%). After four cycles of chemotherapy, a dramatic drop in CTC to a rate of 9% was observed ( P  <   0.01). Pathological complete response (pCR) rate was 40%. No correlation was found between CTC or CEC levels and pCR rate. Median follow-up was 43 months. CTC detection (≥1 CTC/7.5 ml) at baseline was associated with shorter 3-year disease-free survival (39% versus 70% for patients without CTC, P  <   0.01, HR 2.80) and shorter 3-year overall survival (OS) ( P  <   0.01). In multivariate analysis, independent prognostic parameters for shorter survival were absence of hormonal receptors, no pCR and CTC detection at baseline. CEC level at baseline or variations during treatment had no prognostic value. Conclusion: In this pooled analysis of two prospective trials in nonmetastatic IBC, detection rate of CTC was 39% with a strong and independent prognostic value for survival. Combination of pCR after neoadjuvant treatment with no CTC detection at baseline isolated a subgroup of IBC with excellent OS (94% 3-year OS), suggesting that CTC count could be part of IBC stratification in prospective trials.